2013
DOI: 10.1002/psc.2532
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of novel in silico‐developed antimicrobial peptides against a panel of bacterial pathogens

Abstract: Antimicrobial-peptide-based therapies could represent a reliable alternative to overcome antibiotic resistance, as they offer potential advantages such as rapid microbicidal activity and multiple activities against a broad spectrum of bacterial pathogens. Three synthetic antimicrobial peptides (AMPs), AMP72, AMP126, and also AMP2041, designed by using ad hoc screening software developed in house, were synthesized and tested against nine reference strains. The peptides showed a partial β-sheet structure in 10-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
(60 reference statements)
2
22
0
Order By: Relevance
“…The antimicrobial activity of AMP2041 has been reported previously 16,17 on different bacterial and fungal species and in particular, on different PA clinical isolates and ATCC strain 27853. In the present study, the antimicrobial activity of the undiluted and diluted product was evaluated.…”
Section: In Vitro Susceptibility Testingmentioning
confidence: 77%
See 2 more Smart Citations
“…The antimicrobial activity of AMP2041 has been reported previously 16,17 on different bacterial and fungal species and in particular, on different PA clinical isolates and ATCC strain 27853. In the present study, the antimicrobial activity of the undiluted and diluted product was evaluated.…”
Section: In Vitro Susceptibility Testingmentioning
confidence: 77%
“…Maintenance of activity at diluted concentrations is an important feature for antimicrobial agents used on the skin and in the ear canals. 19,20 A prior study of AMP2041 showed bactericidal effect against PA ATCC strain 27853 at an MBC value of 2.14 lg/mL after 2 h of contact time, 17 whereas reported MICs for chlorhexidine digluconate against PA range from 8 to >70 lg/mL. 21 Although Tris-EDTA alone is known to be bacteriostatic, its addition to topical products significantly lowers the MIC and MBC values for several antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further 44 variants of the best candidate D28 were created through systematic charge and hydrophobicity mutations, of which 18 variants demonstrated improved activities against E. coli, B. cereus or S. aureus. In silico approaches that do not rely on the use of an original template sequence have also been reported [68][69][70][71][72]. Hancock's group reported a powerful strategy involving the combination of quantitative structural-activity relationships (QSAR) with machine learning techniques to predict the antimicrobial activities of 100, 000 virtual peptides [68][69][70].…”
Section: Bioinformatics and Combinatorial Library Technologiesmentioning
confidence: 97%
“…The activity of AMP2041 against P. aeruginosa ATCC 27853 was also demonstrated, as well as additivity in combination with levofloxacin [9]. We hypothesized that the reported antimicrobial activity derived from a bacterial membrane damage, but a direct membrane damage was not previously investigated for P. aeruginosa .…”
Section: Introductionmentioning
confidence: 99%